After Progress Perhaps Another Education is Possible: We Can Be Pagans for More Than One Day! - Dennis Atkinson (Nordic Studies in Education)
This paper attempts to bring together a series of ideas/concepts from the work of Isabelle Stengers, Didier Debaise, Jean-Francois Lyotard, Anna Tsing and others in order to apply them to the notion ‘after progress,’ which has some bearing on the theme of this special issue on degrowth. As Savransky and Lundy (2022) argue, ‘the notion of “progress” is arguably the defining idea of modernity’. Whilst this idea of progress has been the object of criticism, its prevalence is still pervasive. But what would living after progress or following a degrowth agenda look like, particularly within contexts of educational policy and practice? After progress perhaps another education is possible. The paper takes on board this suggestion, and rather than viewing education in schools and elsewhere in terms of its current concerns in the West with individual achievement, competition, and standards, we see it as promoting diversity, conviviality, working, thinking, agreeing and disagreeing in common.